A Study of Puberty Health Literacy Level of the First 14-16 Year Girls Grade High School Students in the Eghlid City - Aliyeh zarrinkolah; Forouzandeh Dashti; Heidarali Abedi; Seyed Mohammad Masoudi (Mashhad University of Medical Sciences, 2016)
Background and objective: Health literacy is a global issue, according world health organization’s statement health literacy is central role in determining the health inequality. The overall aim of this study was to" Maturity level of health literacy in 14-16 year girls in first grade of high school. Methods: This descriptive is a quantitative study on 186 girls (14-16 years old) who attend high school in first grade. Sampling method based and designed on a stratified random sample of Morgan. In the course of the study, in order to achieve the desired data, was used from the 5 questionnaire that verification and face and content validity and for reliability of data analysis used from SPSS software (V.18). Results: Overall, this study related to the general level of health literacy and reading understanding puberty (the borderline), skin and hair, genital health (adequate), health, menstruation (far enough) and functional health literacy calculation of the overview of puberty, the skin and hair, genital health (the borderline) healthy menstruation (far enough) and suggests that health literacy on health promotion programs. Calculation of the overall performance of the students in adulthood, independent of reading comprehension and reading comprehension performance and computation between menstrual health, skin and hair, genital health, a significant correlation (P=<0.05) was detected. Conclusion: Adolescent girls' has health literacy level of the borderline city of Eghlid. Teenage girls in puberty due to cross-border health literacy can have many physical and emotional problems that may affect their future health and social reproduction Paper Type: Research Article.